THE EFFECTIVENESS OF DIGITAL-BASED PUBLIC SERVICE INNOVATION: A STUDY OF THE IMPLEMENTATION OF 5G APPLICATIONS IN THE PRIOR LEARNING RECOGNITION PROGRAM AT THE OPEN UNIVERSITY - Muhammad Mahdi Fi Diinillah; Dandan Haryono; Rahmat Hidayat (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
The implementation of Recognition of Prior Learning (RPL) is a strategic public policy in human resource development through the recognition of formal, non-formal, informal learning experiences, and work experience. The Open University developed a 5G application as a digital-based public service innovation to manage the entire RPL process in an integrated manner. This study aims to analyze the effectiveness of the 5G application as a public service innovation in the implementation of the RPL program and its impact on the quality of academic services. The study used a descriptive qualitative approach with data collection techniques through in-depth interviews, observations, and documentation studies of academic staff, assessors, system developers, and students. The analysis was conducted using Sutrisno's program effectiveness theory which includes indicators of program understanding, target accuracy, timeliness, goal achievement, and real change. The results of the study indicate that the 5G application is functionally effective in increasing efficiency, transparency, and integration of RPL services, but is not optimal in terms of timeliness and consistency of assessment.